The Validation of Artificial Intelligence Integrated E-Module with Problem Based Learning Model on Renewable Energy to High School Students’ Critical Thinking Skills - Habil Ihsan (Physics Learning and Education, 2025)
The 21st century demands strong critical thinking, a skill often lacking in Indonesian 10th-grade physics students despite curriculum reforms. Current teaching methods and materials often fall short, failing to adequately engage students and foster these crucial higher-order thinking skills. To bridge this gap, a research project focused on creating and validating an innovative Artificial Intelligence (AI)-integrated e-module, specifically designed for renewable energy topics using a Problem-Based Learning (PBL) model. The goal was to boost high school students' critical thinking. Utilizing the Analysis, Design, and Development (ADDIE) model, the initial phases—analysis, design, and development—were completed, culminating in expert validation. The development process began with a needs analysis at Padang Public Senior High School 4 and a thorough literature review. The design phase involved crafting learning objectives, activities, and an interactive e-module prototype, incorporating AI functionalities and PBL syntax. The e-module was then built using WordPress. Self-evaluation and rigorous validity testing followed, conducted by three expert Physics Lecturers from Universitas Negeri Padang. A "practical guide to develop e-modules" adapted instrument assessed six indicators: material substance, visual communication, software utilization, learning design, PBL model, and AI integration. Data analysis used Cohen's Kappa formula. Validation results confirmed the e-module's high feasibility and quality across all aspects. Scores were consistently high: Material Substance (0.83, very valid), Visual Communication (0.97, very valid), Software Utilization (1.00, very valid), Learning Design (0.92, very valid), Problem-Based Learning Model (0.91, very valid), and AI Integration (0.91, very valid). This demonstrates the e-module's scientific accuracy, engaging design, robust functionality, and effective pedagogical approach. This research successfully validated the AI-integrated e-module with a PBL model as a highly promising teaching material for enhancing critical thinking in renewable energy education.